Efl Students’ Perception Towards Self-Efficacy In Teaching Internship Program With Technology Integration - Yanti, Nur Irma; Husaini, Intan Nor’aini; Eka Putri, Nikmah Sistia (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research was conducted based on the research problem related to the self-efficacy of EFL (English as a Foreign Language) students during their teaching internships with technology integration. This research focuses on students perceive their ability to teach English using digital tools and the factors that contribute to the development of their self-efficacy. The aim of research is to explore EFL students' perceptions of self-efficacy and identify key contributing factors.This research used a qualitative approach with a case study design. The participants were six EFL students from Universitas Muhammadiyah Sampit who had completed their Teaching Internship III. Data were collected through semi-structured interviews and questionnaires. To ensure the validity of the findings, triangulation was applied by comparing the data.The findings indicate that 67% of participants demonstrated high self-efficacy, reinforced by successful teaching experiences and positive responses from students. Meanwhile, 33% of participants exhibited medium self-efficacy in the classroom or nervousness while teaching. The questionnaire data support these findings. Among the four factors, the most dominant is mastery experience (x̅ = 12.00), followed by verbal persuasion (x̅ = 11.67), vicarious experience (x̅ = 11.33), and the least dominant is emotional and physiological states (x̅ = 11.00).